2021
DOI: 10.1021/acssuschemeng.0c07953
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical Alkaline Seawater Oxidation Catalyzed by Cobalt Carbonate Hydroxide Nanorod Arrays with Sequential Proton-Electron Transfer Properties

Abstract: Seawater oxygen evolution is one of the promising energy conversion technologies for large-scale renewable energy storage. It requires efficient catalysts to accelerate the oxygen evolution reaction (OER) for sustained water oxidation, avoiding chlorine evolution under acidic conditions or hypochlorite formation in alkaline solutions. Conventional metal oxide-based OER catalysts follow the adsorbate evolution mechanism that involves concerted proton-electron transfer steps at the active sites. Thus, on the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…In general, the stability of the O* and OO*(V O ) intermediates, which are the key reaction intermediates of the AEM and LOM, respectively, would determine the favorable OER mechanism. 44,45 Specifically, the V O formation step plays an important role in the formation of OO*(V O ) in the LOM, which has been verified by a previous study. 43,46 Further, oxygen vacancy concentration was reported to be an effective parameter in lowing the OER overpotential.…”
Section: ■ Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In general, the stability of the O* and OO*(V O ) intermediates, which are the key reaction intermediates of the AEM and LOM, respectively, would determine the favorable OER mechanism. 44,45 Specifically, the V O formation step plays an important role in the formation of OO*(V O ) in the LOM, which has been verified by a previous study. 43,46 Further, oxygen vacancy concentration was reported to be an effective parameter in lowing the OER overpotential.…”
Section: ■ Discussionsupporting
confidence: 75%
“…In general, the stability of the O* and O O*­(V O ) intermediates, which are the key reaction intermediates of the AEM and LOM, respectively, would determine the favorable OER mechanism. , Specifically, the V O formation step plays an important role in the formation of O O*­(V O ) in the LOM, which has been verified by a previous study. , Further, oxygen vacancy concentration was reported to be an effective parameter in lowing the OER overpotential. The lower formation energy of V O indicates the easier participation of lattice oxygen in the OER, which was also declared from the results of NNO with different orientation surfaces. Following this line of thinking, the V O formation free energy was calculated with the consideration of different surface orientations.…”
Section: Discussionmentioning
confidence: 61%
“…Direct seawater electrolysis can solve severe issues of scarce water supply and high freshwater demand by utilizing fluctuant sustainable energies, particularly in some coastal arid zones. [9][10][11][12] One of the biggest challenges for seawater electrolysis stems from the oxidation of chloride anions including the chlorine evolution reaction (CER) in an acidic electrolyte and the formation of hypochlorite (ClO − ) in an alkaline media, both of which will compete with the OER. [11,[13][14][15] At high pH (>7.5), theoretical overpotentials for the ClO − formation, and OER are linearly related to the pH value with the same slope.…”
mentioning
confidence: 99%
“…In seawater splitting, the HER and OER are associated with local pH variation at the electrode and regarded as a critical issue. [ 33 ] During electrolysis, there has been a continuous reduction in pH at anode due to OH − oxidation and an increment in pH at cathode due to H + reduction. Studies revealed that this pH fluctuation is in 5–9 pH units and triggers severe catalyst degradation even at a small geometric activity.…”
Section: Challenges In Seawater Electrolysismentioning
confidence: 99%
“…Li et al synthesized carbon fiber‐supported cobalt carbonate hydroxide (Co CH@CFP) and compared its selectivity and activity with Ni–Fe layered double hydroxide (LDH) for seawater oxidation. [ 33 ] The Co CH@CFP exhibited high selectivity and activity for OER compared with Ni–Fe LDH. This high performance was explained by the acid–base properties of the catalyst surface determined through the pH shift method.…”
Section: Rational Design Of Anode Materials For Seawater Oxidationmentioning
confidence: 99%